Study on the various lightweight PLA honeycomb structures with 3D printing process conditions - Dikshita Chowdhury; Sunhee Lee (Fashion and Textiles)
Abstract This study focused on creating honeycomb samples using various lightweight polylactic acid (LW_PLA) filaments through 3D printing. A commercial lightweight filaments like PLA(Esun), LW-PLA-ES(Esun), LW-PLA-CL(colorffab), and LW-PLA-HT (colorfab) were used to model 50 mm × 50 mm × 5 mm honeycomb samples, 3D printed with an infill density of 10% and nozzle temperatures ranging from 200 ℃ to 240 ℃ at a 10 ℃ interval. The LW_PLA_CL samples were also printed with different infill densities of 10%, 20%, 30%, 40% and 50% at 230 ℃ and 240 ℃, with a bed temperature of 65 ℃ and a print speed of 60 mm/sec. Characterization involved morphology and compression tests, including surface and foaming analysis via a field emission scanning electron microscope. Compression tests with a universal testing machine revealed that LW_PLA_CL at 240 ℃ and 50% infill density produced the most effective honeycomb structure, offering the best foaming properties and good compressive properties, improving mechanical performance for diverse applications.